A Case of First Episode Psychosis Uncovering Encephalomalacia in a Young Female - Rahul Bansal; Prerna Maheshwari (Indian Journal of Private Psychiatry)
Aim and background: The diagnosis of organic psychosis is made when psychotic symptoms present after a specific neurological or organic event. One such dysfunction of brain structure is encephalomalacia, which refers to softening of brain tissue and can present with varying symptomatology. There is a dearth of cases reported showing quick recovery in patients with organic psychosis attributable to encephalomalacia. Case description: A 25-year-old female presented with acute onset aggressiveness, insomnia, social withdrawal, paranoid ideation, hallucinatory behavior, reduced appetite, and poor self-care. Routine investigations were normal. The computed tomography (CT) scan brain plain revealed encephalomalacia in the left parietal lobe. Organic psychosis was kept as a provisional diagnosis. There was a satisfactory outcome on low-dose antipsychotic on follow-up day 14. She came for follow-up till 3 months and was maintaining well. Conclusion: Encephalomalacia in left parietal lobe region can present with acute psychosis and relatively quick and satisfactory outcome can be seen.